Mechanical behaviour analysis of buried pressure pipeline crossing ground settlement zone. Issue Volume 18:Issued 7(2017) (3rd July 2017) - Zhang, Jie; Liang, Zheng; Han, Chuanjun
Abstract: Numerical simulation model of buried pipeline crossing ground settlement zone was established considering pipeline–soil interaction. Mechanical behaviour of the buried pipeline was investigated, and effects of ground settlement, pipeline parameters and surrounding soil parameters on mechanical behaviour of the buried pipeline were discussed. These results show that there are two high stress areas on both sides of the dividing plane. High stress areas are oval on the top and bottom of the pipeline. Z-shape bending deformation appears under the action of ground settlement. In ground settlement zone, axial strain on the top of the pipeline is compression strain, and axial strain on the bottom of the pipeline is tension strain. On the contrary, they are tension strain and compression strain respectively in no settlement zone. Bending deformation, axial strain and plastic strain of the buried pipeline increase with the increase in ground settlement. Von Mises stress, high stress area, axial strain and plastic strain of the buried pipeline increase with the increasing diameter-thick ratio and internal pressure, but they decrease with the increase in buried depth. Diameter-thick ratio and internal pressure have a small effect on the bending deformation of the buried pipeline. Bending deformation decreases with the increase in buried depth in ground settlement zone. Von Mises stress and high stress area increase with the increasing surrounding soil's elasticity modulus and cohesion, but they increase first and then decrease with the increase in Poisson's ratio. Bending deformation of the pipeline in no settlement zone increases with the increase in elasticity modulus and Poisson's ratio, but it is affected little by the cohesion. Axial strain and plastic strain have a bigger relationship with the elasticity modulus and Poisson's ratio. Axial strain and plastic strain of the buried pipeline increase with the increase in cohesion, and the change rates increase with the increase in ground settlement.